2014
DOI: 10.1016/j.envpol.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar and activated carbon amendment on maize growth and the uptake and measured availability of polycyclic aromatic hydrocarbons (PAHs) and potentially toxic elements (PTEs)

Abstract: With the aim of investigating the effects of carbonaceous sorbent amendment on plant health and end point contaminant bioavailability, plant experiments were set up to grow maize (Zea mays) in soil contaminated with polycyclic aromatic hydrocarbons (PAHs) and metals. Maize and pine derived biochars, as well as a commercial grade activated carbon, were used as amendments. Plant growth characteristics, such as chlorophyll content and shoot to root biomass, improved with sorbent amendment to varying extents and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 41 publications
1
38
0
3
Order By: Relevance
“…Polyoxymethylene and EVA have been used to evaluate biochar effectiveness at reducing polycyclic aromatic hydrocarbons (PAHs) and organochlorine bioavailability. No significant reduction in PAH concentrations in porewater were found by Brennan et al (2014b), and only slight reductions in some DDT (dichlorodiphenyltrichloroethane) metabolites were reported by Andrade et al (2014). However, Wang et al (2013) measured reduced bioavailability of PCBs (polychlorinated biphenyls) using TECAM, and these reductions correlated strongly with reductions in uptake by plant roots.…”
Section: Chemical Methods To Assess Contaminant Mobility and Availabimentioning
confidence: 93%
See 2 more Smart Citations
“…Polyoxymethylene and EVA have been used to evaluate biochar effectiveness at reducing polycyclic aromatic hydrocarbons (PAHs) and organochlorine bioavailability. No significant reduction in PAH concentrations in porewater were found by Brennan et al (2014b), and only slight reductions in some DDT (dichlorodiphenyltrichloroethane) metabolites were reported by Andrade et al (2014). However, Wang et al (2013) measured reduced bioavailability of PCBs (polychlorinated biphenyls) using TECAM, and these reductions correlated strongly with reductions in uptake by plant roots.…”
Section: Chemical Methods To Assess Contaminant Mobility and Availabimentioning
confidence: 93%
“…Reductions in both organic and inorganic contaminant bioaccumulation have been reported in different plant species (e.g., Cucurbita pepo, Brassica napus and Zea mays) after biochar amendment (Brennan et al, 2014b;Denyes et al, 2012;Denyes et al, 2013;Houben et al, 2013a). However, the success of the biochar treatment is likely to depend on the factors previously discussed for earthworms (biochar sorpitive capacity, bioavailability of contaminants in soil before application, species selection, and biochar mixing regime).…”
Section: Plantsmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, Brennan et al (2014) found no detrimental effect of activated carbon derived from coconut shell on soil pH. However, they justified their results based on the application rate, and also recommended a need for testing the activated carbons from different sources as are supposed to show varied potentials on soil pH amendment.…”
Section: Analysis Of Soil Ph Treated With Binding Agentsmentioning
confidence: 80%
“…Con respecto a esto, Brennan et al (2014) encontraron que el contenido en HAP's absorbido por las raíces de las plantas disminuyó considerablemente cuando el suelo fue tratado con un biochar producido a partir de rastrojo de maíz y con carbón activo, en comparación con el uso de un biochar producido a partir de madera de pino donde no se observó una reducción en la absorción de estos compuestos. Como ya se ha comentado, la movilidad y biodisponibilidad de metales disminuye en los suelos tratados con biochar como resultado de diversos procesos entre los que se destacan los cambios en la CIC, el aumento en la capacidad de adsorción, las interacciones electrostaticas o el aumento en el contenido de carbono organico que facilita la formación de complejos entre iones libres y ligandos organicos (Zeng et al, 2015).…”
Section: Evaluación Del Hollín Y Su Efecto Sobre Algunas Especies Vegunclassified